Association of D-dimer and Fibrinogen With Hypercoagulability in COVID-19 Requiring Extracorporeal Membrane Oxygenation. (June 2021) - Chandel, Abhimanyu; Patolia, Saloni; Looby, Mary; Bade, Najeebah; Khangoora, Vikramjit; King, Christopher S.
Background: D-dimer concentration has been used by institutions to identify candidates for intensified anticoagulant treatment for venous thromboembolism prevention and for the mitigation of the microthrombotic complications associated with COVID-19. Thromboelastography (TEG) maximum amplitude (MA) has been validated as a marker of hypercoagulability and MA ≥68 mm has been utilized as a marker of hypercoagulability in other conditions. Methods: The goal of this study was to evaluate the relationship between coagulation, inflammatory, and TEG parameters in patients with COVID-19 on extracorporeal membrane oxygenation (ECMO). We performed a single-center retrospective analysis of consecutive patients that received ECMO for the treatment of COVID-19. TEG, inflammatory, and coagulation markers were compared in patients with and without a thrombotic complication. Correlation tests were performed to identify the coagulation and inflammatory markers that best predict hypercoagulability as defined by an elevated TEG MA. Results: A total of 168 TEGs were available in 24 patients. C-reactive protein and fibrinogen were significantly higher in patients that developed a thrombotic event versus those that did not ( P = 0.04 and P = 0.04 respectively). D-dimer was negatively correlated with TEG MA ( P < 0.01), while fibrinogen was positively correlated ( P < 0.01). A fibrinogen >441 mg/dL was found to have a sensitivity of 91.2% and specificity of 85.7% for the detection of MA ≥68 mm. Conclusions: In critically ill patients with COVID-19 treated with ECMO, D-dimer concentration had an inverse relationship with degree of hypercoagulability as measured by TEG MA. D-dimer elevation may potentially reflect hemostatic perturbation in patients on ECMO or the severity of COVID-19 related sepsis rather than designate patients likely to benefit from anticoagulation. Fibrinogen concentration may represent a more useful marker of hypercoagulability in this population.